MARKET SEGMENTATION ANALYSIS OF ALMOND CRISPY PRODUCTS IN UD PAWON KUE - Taraoktavia, Viyo Tri; Indarwati, Tias (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2021)
MSME competition in the era of globalization is getting tougher. One of them is UD Pawon Kue. Market segmentation is needed to sustain and increase business. This study aims to analyze the market segmentation of crispy almond products at UD Pawon Kue. The study used 200 samples with purposive sampling technique. Data was collected using an online questionnaire. The analysis technique used is cluster analysis with the SPSS program. Based on the research, found three clusters of consumers. The first cluster is called quality-hunting consumers, the second cluster is called uncommitted consumers and the third cluster is loyal customers.